The association between the severity and distribution of white matter lesions and hemorrhagic transformation after ischemic stroke: A systematic review and meta-analysis - Wang, Youjie; Bai, Xueling; Ye, Chen; Yu, Yifan; Wu, Bo (Frontiers in Aging Neuroscience, 2022)
Abstract: Background and Purpose As a part of the natural course of ischemic stroke, hemorrhage transformation (HT) is also a serious complication after reperfusion treatment, which may affect the prognosis of ischemic stroke patients. White matter lesion (WML) refers to focal lesions on neuroimaging and has been suggested to indicate a higher risk of HT. This systematic review and meta-analysis aimed to summarize current evidence on the relation between WML and HT. Methods This systematic review was prepared with reference to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). We searched PubMed, Embase, Web of Science, and Cochrane Library for published studies about WML and HT in ischemic stroke patients. Odds ratios (ORs) and 95% confidence intervals (CIs) from eligible studies were combined to quantify the association between WML severity and the risk of HT. And the descriptive analysis was adopted to evaluate the influence of different WML distributions on predicting HT. Results A total of 2303 articles were identified after removing duplicates through database searching and 41 studies were included in our final analysis. The meta-analysis showed that WML presence was associated with HT (OR = 1.62, 95%CI 1.08-2.43, p = 0.019) and symptomatic intracerebral hemorrhage (sICH) (OR = 1.64, 95%CI 1.17-2.30, p = 0.004), and moderate-to-severe WML indicated a higher risk of HT (OR = 2.03, 95%CI 1.33-3.12, p = 0.001) and sICH (OR = 1.92, 95%CI 1.31-2.81, p < 0.001), respectively. Risk effects of increasing WML severity on both HT and ICH were revealed by the dose-response meta-analysis. In addition, both periventricular (5 of 7 articles) and deep (5 of 6 articles) WML were shown to be associated with HT. Conclusions WML is associated with overall HT and sICH in ischemic stroke patients, and more severe WML indicates a higher risk of HT and sICH. Besides, both periventricular WML and deep WML could be risk factors for HT.